Institutionalizing Wasathiyyah: Translating National Policy on Religious Moderation into Pesantren Educational Ecosystem - Luluk Mashluchah (Pesantren and Community Development Studies - Islamic Institute of Syarifuddin, Indonesia., 2026)
This study aims to analyze the institutionalization process of wasathiyyah through the mechanism of translating national policies on religious moderation into the Islamic Boarding School (Pesantren) education ecosystem. Departing from the gap between macro policies and micro institutional practices, this study uses a qualitative approach with a library research design combined with digital ethnography to examine regulatory documents, pesantren institutional documents, and digital artifacts such as training posters and documentation of peaceful education activities. The analysis was conducted using content analysis techniques with thematic coding to identify patterns of structural adaptation, human resource management, and curriculum transformation in the institutionalization of religious moderation. The findings show that Islamic boarding schools do not act as passive objects of policy, but rather as organizational agents that actively translate indicators of religious moderation into internal rules, educational programs, and institutional culture. Structural adaptation can be seen in the formation of anti-violence regulations, digital ethics, and organizational structures such as curriculum teams and Training of Trainers programs. This study confirms that the institutionalization of wasathiyyah is a managerial process that involves organizational engineering, strengthening the capacity of educators, and integrating the values of moderation into the pesantren education ecosystem in a sustainable manner.